Desarrollo de una propuesta de sistema de tratamiento de aguas residuales generada en la empresa Producción y Gestión S.A.S. (2019)
In this project the proposal of a treatment system for wastewater from the production processes of a cosmetic manufacturing company is made; For this, the diagnosis of industrial wastewater was made, where the critical parameters that do not comply with resolution 0631 of 2015 were determined, which controls the discharge to water bodies. An evaluation of the proposed treatment system was carried out experimentally by simulation at the laboratory level of the equipment required for the development of the treatment system, determining the operating conditions, the necessary reagents and their dosage. After this, the design of the treatment system was carried out through the sizing of the equipment and the dosage of the chemical reagents, finally the costs related to the proposed system were analyzed.